Estimating the effectiveness of a mobile phone network's deferred revenue calculated through the use of a business automation and support system - Smuts, Francois (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MComm (Logistics))--University of Stellenbosch, 2011.